Barriers in Implementing Life Cycle Costing in Malaysia's Green Construction Projects. Issue 1 (1st October 2022) - Maisham, Mysarah; Adnan, Hamimah; Adillah Ismail, Noor Akmal; Asyikin Mahat, Noor Aisyah; Mohd Yussof, Farrah Norizzah
Abstract: Life cycle costing (LCC) is a tool used worldwide to assess the expected economic performance of a building throughout its life cycle. The application of LCC within the construction industry is still lacking, especially in the development of green construction projects despite the many benefits it has been linked to. This paper aims to identify the main barriers in implementing LCC in green construction projects. The research adopted a quantitative method by conducting questionnaires survey distributed through traditional mail and e-mail as well as online platforms to 700 respondents from various backgrounds, namely architects, quantity surveyors, engineers, and other professionals. A total of one hundred and eighty-seven (187) completed and usable questionnaires were collected and analyzed by using frequency descriptive analysis and by mean value using IBM SPSS Statistic 26. The findings indicate that barriers relevant to project clients and the government were the main barriers to LCC implementation in green construction projects. It gives an understanding that both clients and the government play significant roles in promoting the use of LCC. The findings are beneficial to industry practitioners of green developments as a reference to enhance the LCC process and to devise more effective strategies to promote acceptance of LCC in Malaysia's green construction projects.